Cistus salviifolius Toxicity in Cattle. Issue 1 (January 2020) - Mignacca, Sebastian Alessandro; Mucciarelli, Marco; Colombino, Elena; Biasibetti, Elena; Muscia, Salvatore; Amato, Benedetta; Presti, Vincenzo Di Marco Lo; Vazzana, Irene; Galbo, Andrea; Capucchio, Maria Teresa
Toxicity related to consumption of Cistus sp. pl. has been described in ruminants in some countries. This report describes the clinical and pathological findings of Cistus salviifolius toxicosis in 3 beef cattle herds located in 2 different areas of Sicily, Italy. Outbreaks were observed after grazing in poor winter pasture where C. salviifolius was abundant. Mean morbidity and mortality were 29% and 21%, respectively. Most of the affected animals (6 to 36 months old) showed anorexia, weight loss, and pollakiuria culminating in recumbency and death. Occasionally, abortion and neurological signs were observed. In animals with acute signs, there was a moderate decrease of sodium and chloride concentrations in serum. Animals with chronic signs showed an increase of serum urea, creatine phosphokinase (CPK), aspartate transaminase (AST), lactate dehydrogenase (LDH), and phosphorus and a decrease in total serum protein, calcium, chloride, and magnesium concentrations. Moderate anemia and slight neutropenia, lymphocytosis, and eosinophilia were detected in all groups. At necropsy, the main lesion was severe distention of the urinary bladder with turbid hemorrhagic urine and crystalluria. Histologically, chronic cystitis, interstitial nephritis, eosinophilic enteritis, and nonsuppurative necrotizing hepatitis were observed. To our knowledge, this is the first report of C. salviifolius toxicosis in cattle in Italy.